DENGUE FEVER: STAGES, COMPLICATION, DIAGNOSIS, AND PREVENTION STRATEGIES - BISWAS, POULOMI; GANGULY, SANTOSH; DEBNATH, BIPLAB (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Dengue fever virus (DENV) is said to be a single-stranded, positive-sense RNA virus that belongs to the family Flaviviridae and the genus is Flavivirus. The disease can be transmitted through infected blood products and also through organ donation. Vertical transmission (from mother to child) at the time of pregnancy or during birth has been reported. Other unusual reports showed man-to-man modes of transmission. Hemorrhagic fever is specified by hemorrhage, thrombocytopenia, leakage of blood plasma, or dengue shock syndrome. Dengue is basically transmitted by various species of mosquito among the genus Aedes, the most uniquely identified one is Aedes aegypti. There are four different but very closely related serotypes (DENV-1, DENV-2, DENV-3, and DENV-4) of the virus that causes Dengue. Lifelong immunity against the particular serotype that has caused the infection is believed to have been imparted upon recovery. However, cross-immunity to the other serotypes is either partial or temporary upon recovery and hence future infections by any of the other serotypes enhance the risk of developing severe dengue. Prevention is identified by reducing the habitat and the number of mosquitoes and also by limiting exposure to bites. Treatment of mild or moderate type is supportive, with oral or intravenous rehydration. The intravenous fluids and blood transfusion for more severe cases are found to be effective. The present study aimed to present brief and informative salient features of various facts regarding dengue, including its global incidence, structure, mode of transmission, clinical signs and symptoms, control, and preventive measures.